2021
DOI: 10.3390/cells10123333
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Cathelicidin Attenuates High-Fat Diet Plus Alcohol-Induced Liver Injury through FGF21/Adiponectin Regulation

Abstract: Alcohol consumption and obesity are known risk factors of steatohepatitis. Here, we report that the deficiency of CRAMP (cathelicidin-related antimicrobial peptide—gene name: Camp) is protective against a high-fat diet (HFD) plus acute alcohol (HFDE)-induced liver injury. HFDE markedly induced liver injury and steatosis in WT mice, which were attenuated in Camp–/– mice. Neutrophil infiltration was lessened in the liver of Camp–/– mice. HFDE feeding dramatically increased epididymal white adipose tissue (eWAT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…found that after a high-fat diet and one-week binge alcohol gavage, mice lacking cathelicidin-related antimicrobial peptide (CRAMP), an antimicrobial peptide that helps maintain a balanced microbiota, compared to wild-type mice, had elevated FGF21 levels in epididymal white adipose (eWAT) mass and increased serum adiponectin secretion, which has been shown to alleviate hepatic fat deposition and inflammation. 84 Given that after alcohol exposure, hepatic Camp mRNA significantly increased in WT mice, 85 which has been associated with increased reactive oxygen species production, and that FGF21 inhibits oxidative stress through cAMP response element binding protein (CREB) activation, 86 which regulates adiponectin gene expression, 87 a working hypothesis is that CRAMP deficiency upregulates FGF21/CREB/adiponectin signaling to limit alcohol-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…found that after a high-fat diet and one-week binge alcohol gavage, mice lacking cathelicidin-related antimicrobial peptide (CRAMP), an antimicrobial peptide that helps maintain a balanced microbiota, compared to wild-type mice, had elevated FGF21 levels in epididymal white adipose (eWAT) mass and increased serum adiponectin secretion, which has been shown to alleviate hepatic fat deposition and inflammation. 84 Given that after alcohol exposure, hepatic Camp mRNA significantly increased in WT mice, 85 which has been associated with increased reactive oxygen species production, and that FGF21 inhibits oxidative stress through cAMP response element binding protein (CREB) activation, 86 which regulates adiponectin gene expression, 87 a working hypothesis is that CRAMP deficiency upregulates FGF21/CREB/adiponectin signaling to limit alcohol-induced oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…In previous decades, the development of ALD animal models allowed for significant progress to be made in ALD research [ 13 ]. Different ALD models can be used to study the pathogenesis of ALD at different stages [ 135 , 140 , 200 , 201 ]. However, by comparing different ALD models, we found that in models only using an LDE diet, the main changes in animals were limited to early ALD (hepatic steatosis and inflammation), while those of more severe ALD (such as hepatitis and fibrosis) were rarely able to be observed [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“… 176 Similar studies found that FGF21-adiponectin signaling regulates hepatic lipid metabolism, reducing steatohepatitis and the enrichment of inflammatory pathways in high-fat and acute-alcohol-induced liver injury mice. 177 A striking increase in very low-density lipoprotein receptor (VLDLR) can be an indicator of moderate and serious NAFLD, accompanied by endoplasmic reticulum stress. FGF21 protects against serious NAFLD by modulating VLDLR activity by governing endoplasmic reticulum stress.…”
Section: Fgf21-mediated Metabolism In the Livermentioning
confidence: 99%